2010
DOI: 10.3109/08880018.2010.493574
|View full text |Cite
|
Sign up to set email alerts
|

Does Serum Soluble Vascular Endothelial Growth Factor Levels Have Different Importance in Pediatric Acute Leukemia and Malignant Lymphoma Patients?

Abstract: Vascular endothelial growth factor (VEGF) seems to play a central role in angiogenesis-lymphangiogenesis in hematological malignancies. There are limited data related to childhood hematologic malignancies. The aim of the study was to evaluate soluble VEGF (sVEGF) levels in children with acute leukemia and malignant lymphoma (ML) at diagnosis and in remission. The levels of serum sVEGF were measured by enzyme-linked immunosorbent assay (ELISA) in 20 children with acute leukemia, 33 children with different histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
1
6
0
3
Order By: Relevance
“…Its expression is associated with proliferation of neoplastic cells, their invasion and metastasis [ 24 ] VEGF may also play some role in pathogenesis of leukemia, since deregulation of VEGF expression and signaling pathways are observed in ALL [ 25 ]. Our data confirms studies by Kalra et al [ 26 ] and Dincaslan et al [ 27 ], demonstrating that untreated children with ALL have significantly lower VEGF concentration than controls and that, at the end of the induction therapy, VEGF increases to levels similar to controls [ 26 , 27 ]. Hence, we confirm also the hypothesis that since VEGF is expressed in normal hematopoietic cells, the renewal of normal hematopoiesis in the course of therapy may explain the increase in VEGF levels and be a predictor of good response to the chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…Its expression is associated with proliferation of neoplastic cells, their invasion and metastasis [ 24 ] VEGF may also play some role in pathogenesis of leukemia, since deregulation of VEGF expression and signaling pathways are observed in ALL [ 25 ]. Our data confirms studies by Kalra et al [ 26 ] and Dincaslan et al [ 27 ], demonstrating that untreated children with ALL have significantly lower VEGF concentration than controls and that, at the end of the induction therapy, VEGF increases to levels similar to controls [ 26 , 27 ]. Hence, we confirm also the hypothesis that since VEGF is expressed in normal hematopoietic cells, the renewal of normal hematopoiesis in the course of therapy may explain the increase in VEGF levels and be a predictor of good response to the chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…Vascular endothelial growth factor (VEGF) is also highly expressed by malignant lymphoma cells, correlating with disease progression and a negative response to therapy [ 131 , 132 , 133 ]. Circulating serum levels of VEGF are also elevated in lymphoma patients and a predictor of poor prognosis [ 134 , 135 , 136 ]. Mouse models demonstrate that engraftment of NHL directly correlates with tumor VEGF production, and targeting the VEGF pathway with neutralizing antibodies results in inhibition of tumor growth [ 137 , 138 ].…”
Section: Soluble Factorsmentioning
confidence: 99%
“…They concluded that there was a relation between VEGF levels and disease activation. But recent pediatric study is inconclusive about the same point that the VEGF levels of pediatric leukemia patients at diagnosis were lower than remissions by measuring serum soluble VEGF with Elisa [24]. Pruneri et al [22] have found that micro vessel density of MDS patients were lower than AML patients' were, but higher than controls.…”
Section: Discussionmentioning
confidence: 99%
“…Adult studies reveal more trust on VEGF and its prognostic value although studies on children are not [24]. Also there is a different method as PCR, Elisa, and Histopathology that may result in variations in the disease prognosis analyses.…”
Section: Discussionmentioning
confidence: 99%